Kesadaran Etis Mahasiswa Pendidikan Bahasa Inggris dalam Penggunaan Alat Kecerdasan Buatan (AI) untuk Penulisan Esai - Uchy Mukho Adrianty; Pipit Rahayu; Khabib Muafi; Azi Nurazima Juhastri (Cv. Digital Education Nusantara, 2026)
The increasing adoption of generative artificial intelligence (AI) in higher education has created new opportunities for learning and academic writing while raising important ethical concerns. Understanding students’ awareness, knowledge, attitudes, and behaviors related to AI use is essential for promoting responsible and ethical academic practices. This study aimed to examine students’ AI ethics awareness, knowledge of academic policies, attitudes toward AI ethics, and actual behavior in AI-assisted writing. A descriptive quantitative research design was employed using a questionnaire distributed to 21 university students. The collected data were analyzed using descriptive statistics, including mean scores and standard deviations. The findings revealed that all four indicators were categorized as high. AI ethics awareness obtained the highest mean score (M = 3.65, SD = 0.66), followed by attitudes toward AI ethics (M = 3.63, SD = 0.85), actual behavior in AI-assisted writing (M = 3.58, SD = 0.82), and knowledge of academic policies (M = 3.43, SD = 0.75). These results indicate that the respondents generally reported high levels of ethical awareness, positive attitudes toward ethical AI use, adequate knowledge of relevant academic policies, and responsible AI-assisted writing practices. In conclusion, the findings suggest that students demonstrate a positive foundation for the responsible use of AI in academic contexts. The consistently high scores across all indicatorss indicate that ethical awareness, knowledge of academic policies, positive attitudes toward AI ethics, and responsible AI-assisted writing practices are well represented among the respondents.